Long term surface deformation of Soufrière Hills volcano, Montserrat from GPS geodesy : inferences from simple elastic inverse models - Herd, Richard A. (2012)
Campaign and continuous GPS geodetic measurements on Soufrière Hills Volcano, Montserrat are reported from 1995 to 2009, spanning three dome growth and repose episodes. Uniform elastic half-space inversions were used to examine how crustal pressure sources evolved by inverting subsets of all available 3D site data for any given episode using a single Mogi-source. Changes in network topology were also examined. The average best-fitting single Mogi model yields X = 0.3 ± 0.5 km, Y = 0.8 ± 0.4 km, and a depth of Z = 10.4 ± 2.1 km (1-σ, Z positive down), relative to the center of the model domain. The mean Mogi depth for effusive (deflation) versus repose (inflation) is different and significant at >90% confidence, yielding Z = 11.4 ± 2.0 km and 9.3 ± 1.6 km, respectively. A vertical, prolate ellipsoid improves the fit at >95% confidence over a single Mogi source or stacked, two-source model for the 2003–2005 repose and 2005–2007 dome growth episodes.